MACAM-MACAM AKAD DALAM PENERAPANNYA PADA LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Vera Ayu Oktoviasari; Yuman Firmansyah; Amiruddin Kadir; Syaharuddin Syaharuddin (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2025)
Islamic Financial Institutions in Indonesia operate based on Islamic sharia principles, which make contracts the primary basis for every financial transaction. A contract is an agreement or agreement between two parties that is legally and sharia-compliant, and serves as the legal basis for economic activities. This study aims to identify various types of contracts used in Islamic Financial Institutions in Indonesia and analyze their practical application in financial products and services. The research method used is a qualitative study with a descriptive analytical approach. Data were obtained through literature studies, DSN-MUI fatwa documentation, and analysis of practices in Islamic banking, BMT, and Islamic Financial Institutions. The results show that Islamic Financial Institutions in Indonesia use various types of contracts, both tabarru' contracts (benevolent/non-profit contracts) such as Wadiah and Qard, and Tijarah contracts (commercial/profit-oriented contracts) such as Murabahah, Ijarah, and Istishna'. The implementation of these contracts is tailored to product characteristics and customer needs. For example, the murabahah contract is widely applied in consumer financing, while the musyarakah and mudharabah contracts are used in productive business financing. The ijarah contract is commonly used in leasing products, and the wadiah contract is applied in checking account savings products. In practice, several challenges remain, such as limitations in the concept of the contract and the need for Sharia principles to prevent practices that approach usury. This research emphasizes the importance of public education regarding Sharia contracts and the need for more accurate Sharia supervision to ensure consistent implementation of contracts in accordance with Sharia principles. With a proper understanding and implementation of contracts, Sharia financial institutions can continue to grow and provide a fair, transparent, and ethical financial alternative in Indonesia. Keywords : Types of Contracts, Implementation, Islamic Financial Institutions.